The Role of Actinomycetes in Forest Sustainability and Global Ecosystems: A Systematic Review - Arsyka Ramdhiani; Nabila Anindita Putri; Reva Nur Ramadhani; Dwi Westi Rosidha; Faturrahman; Ernin (Samota Journal of Biological Sciences, 2025)
Increasing deforestation in many regions of Indonesia has led to environmental degradation, soil erosion, and a higher risk of flash floods. In addition to vegetation cover, soil microorganisms play a crucial role in maintaining forest ecosystem functions, particularly Actinomycetes. This study aims to examine the role of soil Actinomycetes in supporting forest ecosystem sustainability, with a focus on their ability to solubilize phosphate, improve and stabilize soil structure, and contribute to the mitigation of environmental impacts caused by deforestation. A systematic review approach was applied by analyzing scientific articles obtained from five databases, comprising 35 journals, of which 17 were identified as relevant. The selected articles were screened based on predefined inclusion criteria and analyzed descriptively. The results indicate that Actinomycetes significantly enhance nutrient availability, especially phosphate, improve soil physical properties by increasing aggregation, porosity, and water infiltration capacity, and support forest health through the production of bioactive compounds that suppress plant pathogens. Overall, soil Actinomycetes play a fundamental role in maintaining soil stability and forest ecosystem sustainability and have strong potential to be utilized in sustainable forest management and environmental conservation strategies